Recent Progress in Metal-Organic Frameworks for the Fabrication of Chemical Sensors - Ahmad, Khursheed; Khan, Mohd Quasim; Raza, Waseem; Gondal, M. A. (American Chemical Society, 2021)
Quantifying Contaminants with MOFs. Metal-organic frameworks (MOFs) have emerged as highly customizable catalysts based on their unique features. Recent studies have developed specific MOFs for many applications. As part of a three-volume set (1393-1395), this volume provides an overview on MOFs used in environmental sensing, including synthesis, characterization, and examples of applications. Materials scientists, chemical engineers, and environmental scientists will find this work useful, as will students learning about this active area of research.
CRIS-Team Scopus Importer:2021-12-03